2014
DOI: 10.1038/srep03739
|View full text |Cite
|
Sign up to set email alerts
|

TUSC3 Loss Alters the ER Stress Response and Accelerates Prostate Cancer Growth in vivo

Abstract: Prostate cancer is the most prevalent cancer in males in developed countries. Tumor suppressor candidate 3 (TUSC3) has been identified as a putative tumor suppressor gene in prostate cancer, though its function has not been characterized. TUSC3 shares homologies with the yeast oligosaccharyltransferase (OST) complex subunit Ost3p, suggesting a role in protein glycosylation. We provide evidence that TUSC3 is part of the OST complex and affects N-linked glycosylation in mammalian cells. Loss of TUSC3 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 45 publications
4
74
1
Order By: Relevance
“…A recent reports confirms that TUSC3 is a subunit of the OST complex, and shows that loss of TUSC3 is associated with alterations in ER homeostasis, enhanced migration of cells, and increased tumor formation in nude mouse xenograft model [47]. …”
Section: Magt1 and Tusc3 Are Oxidoreductase Subunits Of The Stt3b Commentioning
confidence: 80%
“…A recent reports confirms that TUSC3 is a subunit of the OST complex, and shows that loss of TUSC3 is associated with alterations in ER homeostasis, enhanced migration of cells, and increased tumor formation in nude mouse xenograft model [47]. …”
Section: Magt1 and Tusc3 Are Oxidoreductase Subunits Of The Stt3b Commentioning
confidence: 80%
“…The full-length MAGT1 protein has 367 amino acids, a large amino-terminal segment, 4 TM domains, and a small carboxy-terminal tail (29, 30). Mutations in TUSC3 have been associated with nonsyndromic autosomal recessive retardation (3134), prostate cancer (35), and ovarian cancer (36, 37), which have not been observed in XMEN disease.…”
Section: Geneticsmentioning
confidence: 99%
“…In contrast, the TUSC3 subunit has been identified as a tumour suppressor in several cancer types (Kratochvilova et al 2015, Fan et al 2016, Jiang et al 2016. Although there is no reported evidence to date linking RPN2 or STT3A to prostate cancer, TUSC3 has been shown to act as a tumour suppressor in prostate cancer cells and is downregulated in prostate tumours (Horak et al 2012(Horak et al , 2014.…”
Section: N-glycan Biosynthesis (Ost Complex N-glycan Processing)mentioning
confidence: 94%
“…In prostate cancer, the sTn antigen is detected in up to half of all high-grade tumours (Myers et al 1994, Genega et al 2000, and (Kratochvilova et al 2015), pancreatic cancer (Fan et al 2016), glioblastoma (Jiang et al 2016). Overexpressed in colorectal cancer cells -induces EMT, tumour growth and invasion (Gu et al 2016) Downregulated in prostate cancer tissue -acts as a tumour suppressor (Horak et al 2012(Horak et al , 2014 N-glycan processing EDEM3 Mannose trimming of N-glycans Not reported in other cancers Upregulated in malignant PCa as part of a glycosylation gene signature (Barfeld et al 2014a). Androgen regulated and linked to prostate cancer cell viability .…”
Section: :3mentioning
confidence: 99%